Digital Curation and Creative Brokering: Managing information overload in open organizing. Issue 1 (January 2023) - Lingo, Elizabeth L.
While open organizing offers great promise for harnessing diverse and previously untapped knowledge and perspectives in strategy and innovation processes, how leaders manage the fundamental problem of information overload within these efforts remains unexplored. In this qualitative study, I develop a model of digital curation as creative brokering—how leaders strategically select, share, and interpret digital material across a diffuse network of actors to achieve concerted strategic action in the face of information overload. More specifically, I identify five digital curation practices—spotlighting, amplifying, refuting, recapping, and refocusing—and show why and how these practices are used in combination over time to respond to differing information overload challenges arising as open organizing unfolds. The paper's contributions are threefold. First, it advances open organizing scholarship by showing how leaders engage in digital curation to build shared understanding, nurture ownership and ongoing commitment, and foster concerted action in the face of information overload. Second, it springboards research on the behavioral practice and process of brokerage within open organizing networks. Third, it highlights the critical role of managing emotions, in addition to information and knowledge exchange, in brokerage and open organizing processes.